Galvanized steel sheet, component, and manufacturing method thereof
A galvanized steel sheet with a specific microstructure and controlled composition addresses the trade-off between strength and ductility, enhancing both uniform and local deformation characteristics, and improving corrosion resistance, making it suitable for automotive applications.
Patent Information
- Application Number
- JP2023565464
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-31
- Filing Date
- 2022-12-26
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-12-26
AI Technical Summary
Existing high-strength steel sheets used in automobiles face challenges with both uniform and local deformation characteristics, particularly in forming methods like stretch flange forming and bending, due to the trade-off between strength and ductility, and there is a need for improved corrosion resistance.
A galvanized steel sheet with a specific microstructure comprising high Mn ferrite and controlled hydrogen content, along with a balanced composition of elements like C, Si, Mn, and Al, is produced using a continuous annealing and hot-dip galvanizing process, enhancing both uniform and local deformation characteristics.
The steel sheet achieves a tensile strength of 980 MPa or more with excellent uniform and local deformation characteristics, improving formability and corrosion resistance, suitable for automotive applications.
Smart Images

Figure 0007619483000010 
Figure 0007619483000011 
Figure 0007619483000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-strength galvanized steel sheet having excellent ductility for use as an automotive steel sheet, a high-strength member, and a method for producing the same. [Background technology]
[0002] In recent years, from the viewpoint of protecting the global environment, improving the fuel efficiency of automobiles has become an important issue. Accordingly, there has been a growing movement to reduce the weight of the automobile body itself by increasing the strength of the automobile body materials to make them thinner. However, increasing the strength of steel sheets leads to a decrease in ductility, i.e., a decrease in formability. For this reason, there is a demand for the development of materials that combine high strength and high formability. Furthermore, in light of the recent increasing demand for improved corrosion resistance in automobiles, there has been much development of high-tensile steel sheets that are hot-dip galvanized.
[0003] In response to such demands, various dual-phase high-strength steel sheets have been developed, such as dual-phase steels (DP steels) of ferrite and martensite and TRIP steels that utilize the transformation-induced plasticity of retained austenite. For example, Patent Document 1 discloses a high-strength hot-dip galvanized steel sheet with a DP structure of ferrite and martensite that has high workability. Furthermore, Patent Document 2 proposes a galvannealed steel sheet with excellent workability that achieves high ductility by adding a large amount of Si to ensure retained γ.
[0004] However, although DP steels and TRIP steels have excellent uniform deformation properties, they have a problem of poor local deformation properties. Local deformation properties are the deformation properties from the time when necking occurs in the final stage of uniform deformation and deformation progresses locally to the time of fracture, and poor local deformation properties lead to poor stretch flangeability and bendability. In particular, stretch flange forming and bending are important forming methods for high-strength steel sheets, and it is important to improve local deformation properties in addition to uniform deformation properties. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2010-106323 A [Patent Document 2] Japanese Patent Application Publication No. 11-279691 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a galvanized steel sheet, a member, and a manufacturing method thereof that have excellent uniform deformation characteristics and localized deformation characteristics and a tensile strength TS of 980 MPa or more.
[0007] Here, the tensile strength TS is based on the JIS Z2241 (2011) standard and is measured at a strain rate of 10 -3 This refers to the tensile strength obtained by performing a tensile test at 1000 kPa / s. Excellent uniform deformation characteristics are defined as those that meet the requirements of JIS Z2241 (2011) and are -3 This means that the product TS × T.El of the total elongation T.El obtained by performing a tensile test at 1000 MPa / s and the tensile strength TS mentioned above is 17000 MPa·% or more. Excellent local deformation characteristics are defined as those that meet the requirements of JIS Z2241 (2011) and are measured at a strain rate of 10 -3 / s, and the ultimate deformability εl calculated from the following formula (2) is 0.70 or more. εl=-{ln(W / W0)+ln(T / T0)} ···(2) Here, εl is the ultimate deformability, W is the width (mm) of the fracture surface of the tensile test specimen after the tensile test, W0 is the width (mm) of the tensile test specimen before the tensile test, T is the thickness (mm) of the fracture surface of the tensile test specimen after the tensile test, and T0 is the thickness (mm) of the tensile test specimen before the tensile test. [Means for solving the problem]
[0008] The present inventors have conducted extensive research from the viewpoints of the component composition and microstructure of steel sheets in order to produce dual-phase high-strength steel sheets excellent in ductility using a continuous annealing line or a continuous hot-dip galvanizing line. As a result, it was found that by including high-Mn ferrite with a high Mn concentration in addition to low-Mn ferrite in the microstructure of dual-phase high-strength steel plate, and by reducing the amount of diffusible hydrogen in the steel, it is possible to improve both the uniform and localized deformation characteristics. Ferrite is a soft phase with low C and Mn concentrations compared to hard phases such as martensite, and is an effective phase for improving uniform deformation characteristics. However, since ferrite has a large difference in hardness from hard phases such as martensite, voids are easily generated at the interface, and the connection of the generated voids leads to a decrease in local deformation characteristics. In response to such a problem, the present inventors have found that by including a specific amount of high Mn ferrite, whose Mn concentration is 1.05 to 2.5 times the Mn concentration (Mn content) of the steel sheet, it is possible to significantly improve local deformation characteristics while maintaining high uniform deformation characteristics. Although the mechanism of the improvement of local deformation characteristics by including high Mn ferrite is not clear, it is possible that the generation of high Mn ferrite is effective against the generation of voids at the interface between ferrite and martensite. Furthermore, it has been found that reducing the amount of diffusible hydrogen in steel is effective for improving ductility, and in particular, the local deformation characteristics are greatly improved.
[0009] The present invention has been made based on the above findings. [1] A galvanized steel sheet comprising a steel sheet and a galvanized layer formed on the steel sheet, The steel plate is In mass%, C: 0.08% or more and 0.3% or less, Si: 0.5% or more and 3.0% or less, Mn: 2.0% or more and 3.5% or less, P: 0.1% or less, S: 0.01% or less, Al: 0.01% or more and 0.1% or less, N: Contains 0.015% or less, The balance is Fe and unavoidable impurities. The area ratio of ferrite is 20% or more and 70% or less, The area ratio of martensite is 30% or more and 80% or less, The ferrite is low-Mn ferrite having a Mn concentration of 0.80 to 0.95 times the Mn content of the steel plate; and high Mn ferrite having a Mn concentration of 1.05 to 2.5 times the Mn content of the steel plate, The ratio of the low Mn ferrite to the entire ferrite is 20% or more and 80% or less in terms of area ratio, and The ratio of the high Mn ferrite to the entire ferrite is 20% or more and 80% or less in terms of area ratio, The average grain size of the martensite is 10 μm or less, A galvanized steel sheet having a diffusible hydrogen content of 0.30 mass ppm or less. [2] The component composition is In mass%, Ti: 0.2% or less, The galvanized steel sheet according to the above [1], containing one or two selected from the group consisting of Nb: 0.2% or less. [3] The component composition is In mass%, Cr: 1.0% or less, Mo: 1.0% or less V: 1.0% or less. [4] The component composition is In mass%, B: The galvanized steel sheet according to any one of [1] to [3] above, containing 0.005% or less. [5] The component composition is In mass%, Ca: 0.005% or less, The galvanized steel sheet according to any one of the above [1] to [4], containing one or two selected from the group consisting of Sb: 0.03% or less. [6] When the surface layer of the steel plate is a region of 200 μm or less from the surface of the steel plate in the plate thickness direction, The surface layer has a soft surface layer having a Vickers hardness of 85% or less of the Vickers hardness at a quarter of the plate thickness position, When the nano hardness was measured at 300 points or more in a 50 μm × 50 μm region of the sheet surface at a 1 / 4 position and a 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the steel sheet, The ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface to the total number of measurements at 1 / 4 of the sheet thickness direction depth of the soft surface layer is 0.10 or less, Furthermore, the standard deviation σ of the nanohardness of the sheet surface at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, The galvanized steel sheet according to any one of the above [1] to [5], wherein the standard deviation σ of the nano-hardness of the sheet surface at a position half the depth in the sheet thickness direction of the soft surface layer from the surface of the steel sheet is 2.2 GPa or less. [7] The zinc-plated steel sheet according to any one of [1] to [6], having a metal plating layer formed between the steel sheet and the zinc plating layer on one or both sides of the zinc-plated steel sheet. [8] The zinc plating layer is The Fe content is 8-15% by mass, and the coating weight per side is 20-120g / m 2 The zinc-plated steel sheet according to any one of the above [1] to [7], [9] A member made using the zinc-plated steel sheet according to any one of [1] to [8] above.
[10] A hot rolling process in which a steel slab having a chemical composition according to any one of [1] to [5] is hot rolled to obtain a hot rolled steel sheet having a structure in which the sum of the area ratios of bainite and martensite is 80% or more; A pickling process for pickling the obtained hot-rolled steel sheet; A cold rolling process in which cold rolling is performed at a cold rolling reduction rate of 30% or more and 80% or less after the pickling process to obtain a cold-rolled steel sheet; A continuous annealing process for subjecting the cold-rolled steel sheet to continuous annealing; After the continuous annealing step, the obtained cold-rolled annealed steel sheet is cooled to 550 ° C. or less at an average cooling rate of 3 ° C. / s or more and 50 ° C. / s or less in a temperature range of 750 to 550 ° C.; a galvanizing step of performing a galvanizing treatment after the first cooling step; A second cooling step of cooling the plated steel sheet after the zinc plating step to 100°C or less; A reheating step of holding the plated steel sheet after the second cooling step in a temperature range of 150°C to 450°C for 10 seconds to 72 hours, In the continuous annealing step, The average heating rate between 500 and 700°C is 3°C / s or more. At 780°C or higher and lower than 940°C, D in the following formula (1) is 1.0×10 -6 Above 8.0×10 -6 Satisfy the following: Heat to a maximum temperature of 780℃ or higher and (Ac3 point -20℃) or lower. A method for manufacturing a galvanized steel sheet, in which the hydrogen concentration in an annealing furnace in a temperature range of 780°C or higher is 1 vol% or more and 20 vol% or less.
number
[11] The method for producing a galvanized steel sheet according to
[10] , wherein the continuous annealing in the continuous annealing step is carried out in an atmosphere with a dew point of -30°C or higher.
[12] The method for producing a galvanized steel sheet according to
[10] or
[11] , further comprising a metal plating step of applying metal plating to one or both sides of the cold-rolled steel sheet after the cold rolling step and before the continuous annealing step to form a metal plating layer.
[13] A method for producing a galvanized steel sheet according to any one of the items
[10] to
[12] , comprising an alloying treatment step of subjecting the plated steel sheet after the galvanizing step and before the second cooling step to an alloying treatment in a temperature range of 480 to 560°C for 5 to 60 s.
[14] A method for producing a component, comprising the step of subjecting the zinc-plated steel sheet according to any one of [1] to [8] above to at least one of forming and joining to produce a component. Effect of the Invention
[0010] According to the present invention, there are provided a galvanized steel sheet, a member, and a method for producing the same, which have excellent uniform deformation properties and local deformation properties and a tensile strength TS of 980 MPa or more. The galvanized steel sheet of the present invention can be suitably used as a material for automobile parts. [Brief description of the drawings]
[0011] [Figure 1] 1A is a diagram for explaining the U-bending (primary bending) in the U-bending + contact bending test of the embodiment (embodiment 2), and FIG. 1B is a diagram for explaining the contact bending (secondary bending) in the U-bending + contact bending test of the embodiment (embodiment 2). [Diagram 2] 1A is a diagram for explaining a V-bending process (primary bending process) in a V-bending + orthogonal VDA bending test of an embodiment (embodiment 2), and FIG. 1B is a diagram for explaining an orthogonal VDA bending process (secondary bending process) in a V-bending + orthogonal VDA bending test of an embodiment (embodiment 2). [Diagram 3] 3(a) is a front view of a test member produced for the axial crush test of the embodiment (Example 2) in which a hat-shaped member and a steel plate are spot-welded, (b) is a perspective view of the test member shown in Fig. 3(a), and (c) is a schematic diagram for explaining the axial crush test of the embodiment (Example 2). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be specifically described below.
[0013] [Zinc-plated steel sheet] The galvanized steel sheet of the present invention is a galvanized steel sheet comprising a steel sheet and a galvanized layer formed on the steel sheet, the steel sheet having a composition containing, by mass%, C: 0.08% or more and 0.3% or less, Si: 0.5% or more and 3.0% or less, Mn: 2.0% or more and 3.5% or less, P: 0.1% or less, S: 0.01% or less, Al: 0.01% or more and 0.1% or less, N: 0.015% or less, with the balance being Fe and unavoidable impurities, and having a structure in which the area ratio of ferrite is 20% or more and 70% or less and the area ratio of martensite is 30% or more and 80% or less, The steel sheet is characterized in that it has low-Mn ferrite having a Mn concentration of 0.80 to 0.95 times the Mn concentration (Mn content) of the steel sheet, and high-Mn ferrite having a Mn concentration of 1.05 to 2.5 times the Mn concentration (Mn content) of the steel sheet, the ratio of the low-Mn ferrite to the entire ferrite being 20% to 80% in terms of area ratio, and the ratio of the high-Mn ferrite to the entire ferrite being 20% to 80% in terms of area ratio, respectively, the average crystal grain size of martensite is 10 μm or less, and the amount of diffusible hydrogen in the steel is 0.30 ppm by mass or less.
[0014] First, the reason why the composition of the steel sheet in the present invention is limited to the above range will be described. Note that "%" regarding the composition means mass % unless otherwise specified.
[0015] C: 0.08% or more and 0.3% or less C is an essential element for generating martensite and ensuring the desired strength, and therefore the C content must be 0.08% or more. On the other hand, if the C content exceeds 0.3%, it leads to a decrease in weldability. Therefore, the C content is set to 0.08% or more and 0.3% or less. The C content is preferably 0.10% or more. In addition, the C content is preferably 0.25% or less, and more preferably 0.20% or less.
[0016] Si: 0.5% or more and 3.0% or less Si is an element effective in strengthening steel, and is also useful for the formation of high Mn ferrite. Such effects can be obtained when the Si content is 0.5% or more. On the other hand, if the Si content exceeds 3.0%, the surface properties deteriorate due to the Si-based scale formed during hot rolling. Therefore, the Si content is set to 0.5% or more and 3.0% or less. The Si content is preferably 0.7% or more. Also, the Si content is preferably 2.0% or less.
[0017] Mn: 2.0% or more and 3.5% or less Mn is an element effective in strengthening steel, and is also necessary for the formation of high-Mn ferrite. In order to secure the desired effect, the Mn content must be 2.0% or more. On the other hand, if the Mn content exceeds 3.5%, it will lead to a decrease in weldability and formability. Therefore, the Mn content is set to 2.0% or more and 3.5% or less. The Mn content is preferably 2.2% or more. Also, the Mn content is preferably 3.0% or less.
[0018] P:0.1% or less P is an effective element for strengthening steel, but if the P content exceeds 0.1%, it leads to a decrease in workability and toughness. Therefore, the P content is set to 0.1% or less. The P content is preferably 0.05% or less, and more preferably 0.02% or less. On the other hand, the lower limit of the P content is not particularly limited, but it is preferably set to 0.003% or more from the viewpoint of production costs.
[0019] S: 0.01% or less Since S becomes inclusions such as MnS and leads to a decrease in formability, it is better to keep the S content as low as possible, and the S content is set to 0.01% or less. The S content is preferably 0.005% or less, and more preferably 0.003% or less. On the other hand, the lower limit of the S content is not particularly limited, but it is preferably 0.0003% or more from the viewpoint of manufacturing costs.
[0020] Al: 0.01% or more and 0.1% or less Al acts as a deoxidizer and is an element effective in improving the cleanliness of steel, and is preferably added in the deoxidization process. If the Al content is less than 0.01%, the effect of the addition is poor, so the lower limit of the Al content is set to 0.01%. The Al content is preferably 0.02% or more. On the other hand, excessive addition of Al deteriorates the quality of the slab during steelmaking. Therefore, the Al content is set to 0.1% or less. The Al content is preferably 0.06% or less.
[0021] N: 0.015% or less If the N content exceeds 0.015%, coarse AlN increases inside the steel sheet, and fatigue properties deteriorate. Therefore, the N content is set to 0.015% or less. The N content is preferably 0.010% or less. On the other hand, the lower limit of the N content is not particularly limited, but the N content is preferably 0.001% or more.
[0022] The steel sheet of the present invention has the above-mentioned components, with the balance including Fe (iron) and unavoidable impurities. In particular, the steel sheet according to one embodiment of the present invention preferably has a composition containing the above-mentioned components, with the balance including Fe (iron) and unavoidable impurities.
[0023] The steel sheet of the present invention may contain, as optional elements, one or more selected from the following (A), (B), (C) and (D) depending on the desired properties. (A) by mass%, one or two selected from Ti: 0.2% or less, Nb: 0.2% or less, (B) one or more selected from, by mass%, Cr: 1.0% or less, Mo: 1.0% or less, and V: 1.0% or less; (C) Mass%, B: 0.005% or less, (D) In mass%, one or two selected from Ca: 0.005% or less, Sb: 0.03% or less
[0024] One or two selected from Ti: 0.2% or less, Nb: 0.2% or less Ti and Nb are added for the purpose of increasing the strength of steel by precipitation strengthening. In order to secure the desired strength, when Ti and Nb are contained, the Ti content and Nb content are preferably 0.01% or more. On the other hand, when the Ti and Nb elements are contained in an amount exceeding 0.2%, not only the effect is saturated but also the formability is deteriorated. Therefore, when Ti and Nb are contained, the Ti content and Nb content are each 0.2% or less. The Ti content and Nb content are each preferably 0.03% or more. Moreover, the Ti content and Nb content are each preferably 0.1% or less.
[0025] One or more selected from the following: Cr: 1.0% or less, Mo: 1.0% or less, V: 1.0% or less Cr, Mo, and V are elements that increase hardenability and are effective in strengthening steel. This effect can be obtained by making the Cr content 0.05% or more, the Mo content 0.05% or more, and the V content 0.01% or more. Therefore, it is preferable that the Cr content is 0.05% or more, the Mo content is 0.05% or more, and the V content is 0.01% or more. The Cr content is preferably 0.1% or more. The Mo content is preferably 0.1% or more. The V content is preferably 0.02% or more. However, if the Cr content, Mo content, and V content each exceed 1.0%, the formability decreases. Therefore, when Cr, Mo, and V are contained, the Cr content, Mo content, and V content are each set to 1.0% or less. The Cr content is preferably 0.5% or less. The Mo content is preferably 0.5% or less. The V content is preferably 0.5% or less.
[0026] B: 0.005% or less B is an element that has the effect of improving hardenability, and can be contained as necessary. Such an effect can be obtained when the B content is 0.0003% or more. Therefore, the B content is preferably 0.0003% or more. The B content is more preferably 0.001% or more. However, if the content of B exceeds 0.005%, the effect becomes saturated and the cost increases, so if B is contained, the B content is set to 0.005% or less, and preferably 0.003% or less.
[0027] Ca: 0.005% or less, Sb: 0.03% or less Ca is an element that is effective in making the shape of sulfides spheroidal and improving the adverse effect of sulfides on moldability, and can be contained as necessary. This effect can be obtained by making the Ca content 0.001% or more. However, if Ca is contained in an amount exceeding 0.005%, it causes an increase in inclusions, etc., and causes surface and internal defects, etc. Therefore, if Ca is contained, the Ca content is set to 0.005% or less. Sb has the effect of suppressing the formation of a decarburized layer in the surface layer of the steel sheet and improving fatigue properties. In order to realize such an effect, the Sb content is preferably 0.003% or more. However, if the Sb content exceeds 0.03%, it will lead to an increase in the rolling load during the production of the steel sheet, and there is a concern that productivity will decrease. Therefore, if Sb is contained, the Sb content is set to 0.03% or less. The Sb content is preferably 0.005% or more. Also, the Sb content is preferably 0.02% or less.
[0028] When any of the above optional elements is contained in an amount less than the aforementioned preferred lower limit, the element is considered to be contained as an unavoidable impurity.
[0029] Next, the structure of the steel sheet of the zinc-plated steel sheet of the present invention will be described.
[0030] Area ratio of martensite: 30% to 80% Martensite acts to increase the strength of steel, and in order to obtain the desired strength, the area ratio must be 30% or more. On the other hand, if the area ratio of martensite exceeds 80%, formability decreases. Therefore, the area ratio of martensite is set to 30% or more and 80% or less. The martensite is preferably 40% or more. Also, the martensite is preferably 70% or less.
[0031] Average grain size of martensite: 10μm or less In addition, the refinement of martensite is effective in improving local deformation characteristics. Such an effect can be obtained when the average grain size of martensite is 10 μm or less, so the average grain size of martensite is set to 10 μm or less. The average grain size of martensite is preferably 7 μm or less. Although there is no particular lower limit, the average grain size of martensite is preferably 1 μm or more, and more preferably 2 μm or more. In the present invention, the martensite may be either fresh martensite that is as quenched or tempered martensite that is tempered, and there is no problem even if both are mixed.
[0032] Ferrite area ratio: 20% to 70% In order to ensure good uniform elongation properties, the total area ratio of ferrite needs to be 20% or more. On the other hand, if the area ratio of ferrite exceeds 70%, it becomes difficult to obtain the desired strength. Therefore, the area ratio of ferrite is set to 20% or more and 70% or less. The ferrite is preferably 30% or more. Also, the ferrite is preferably 60% or less. Note that ferrite here refers to all ferrite (all ferrite) including high Mn ferrite and low Mn ferrite described later, and all ferrite also includes ferrite that does not fall into either high Mn ferrite or low Mn ferrite.
[0033] Ratio of area ratio of low Mn ferrite to area ratio of total ferrite: 20% to 80% Ratio of area ratio of high Mn ferrite to area ratio of total ferrite: 20% to 80% In the present invention, low-Mn ferrite refers to ferrite in which the Mn concentration is 0.80 to 0.95 times the Mn concentration (Mn content) of the steel sheet. In the present invention, low-Mn ferrite refers to ferrite in which the Mn concentration is 1.05 to 2.5 times the Mn concentration (Mn content) of the steel sheet. By mixing low Mn ferrite and high Mn ferrite in a ratio of 20 to 80% of the total ferrite, both the uniform deformation characteristics and the local deformation characteristics are improved. If the ratio of low Mn ferrite or high Mn ferrite to the total ferrite is less than 20% or exceeds 80%, the above-mentioned effects cannot be obtained, so the ratio of low Mn ferrite and high Mn ferrite to the total ferrite is set to 20 to 80% in area ratio. Preferably, this ratio is 30% or more. Also, preferably, this ratio is 70% or less.
[0034] The method for measuring the structure (cross-sectional structure of steel plate) is to first reveal the structure with a 1% by mass solution of nital, and then observe the 1 / 4 position of the plate thickness (a position at a depth equivalent to one-quarter of the plate thickness from the surface) at a magnification of 3000x using a scanning electron microscope (SEM), and quantify the area ratios of martensite, ferrite, pearlite, and bainite from the photograph of the structure taken. As for other structures, the volume fraction of retained austenite is determined by polishing the steel plate up to 1 / 4 of the plate thickness direction and measuring the diffracted X-ray intensity at this 1 / 4 plate thickness surface. CoKα rays are used as the incident X-rays, and intensity ratios are calculated for all combinations of integrated peak intensities of the {111}, {200}, {220}, and {311} planes of the retained austenite phase and the {110}, {200}, and {211} planes of the ferrite phase, and the average of these is taken as the volume fraction (area fraction) (%) of retained austenite. The average grain size of martensite was measured by observing the specimen at a magnification of 3000 times using a SEM and taking a structural photograph. The grain size was determined to be between 5000 and 10000 μm. 2 The area and number of martensite grains in the field of view are obtained, and the area is divided by the number to obtain the area per martensite grain. One side of the martensite grain approximated as a square is taken as the average grain size.
[0035] The proportion of low Mn ferrite and high Mn ferrite in the total ferrite is calculated as follows. First, a sample was taken from the cross section of the steel plate parallel to the rolling direction, and the observation surface was mechanically polished to a mirror finish. After that, the sample was analyzed by FE-EPMA in the range of 1 / 8 to 3 / 8 of the plate thickness, and the thickness was measured from 5000 to 10000 μm. 2 The distribution of Mn concentration in the field of view is measured at intervals of 0.1 μm. From these, measurement points corresponding to the positions of ferrite are extracted, and further measurement points whose concentration is 0.80 to 0.95 times or 1.05 to 2.5 times the Mn concentration (Mn content) of the steel are extracted. The ratios of the number of measurement points that are 0.80 to 0.95 times or 1.05 to 2.5 times the Mn concentration of the steel to the number of measurement points in the entire ferrite are calculated as the ratios of the area ratio of low Mn ferrite and the area ratio of high Mn ferrite to the area ratio of the entire ferrite, respectively. The location of ferrite in the area where the Mn FE-EPMA analysis was performed is not particularly limited to a specific method, but can be identified by, for example, measuring the C concentration distribution with FE-EPMA. Normally, quantitative evaluation of carbon concentration using FE-EPMA analysis is difficult due to the effect of contamination (carbon contamination) from hydrocarbons that accumulate at the analysis points on the sample surface during measurement, but the method disclosed in "Tetsu to Hagane, 103 (2017), p. 622" makes it possible to quantitatively analyze the carbon concentration while avoiding carbon contamination. Since carbon is almost insoluble in ferrite, areas with low carbon concentration (areas where the carbon concentration is 0.15 mass% or less) become ferrite.
[0036] In the present invention, so long as the above phase constitution is satisfied, phases other than those mentioned above, such as bainite, retained austenite, and pearlite, may be contained in an area ratio of 10% or less.
[0037] Diffusible hydrogen content in steel: 0.30 mass ppm or less The steel plate has a diffusible hydrogen content of 0.30 ppm by mass (mass ppm) or less, as measured by the method described below. Diffusible hydrogen in steel not only deteriorates hydrogen embrittlement resistance, but also reduces ductility, particularly local deformation characteristics, if the diffusible hydrogen content in steel exceeds 0.30 ppm by mass and becomes excessive. Therefore, in the present invention, the diffusible hydrogen content in steel is set to 0.30 ppm by mass or less, and preferably 0.20 ppm by mass or less. There is no particular lower limit, but the lower the better. The amount of diffusible hydrogen in steel is measured using the following method. First, a 5 x 30 mm test piece is cut out from a plated steel sheet. Next, a router is used to remove the plating from the surface of the test piece and it is placed in a quartz tube. Next, the inside of the quartz tube is purged with Ar, and the temperature is raised at 200°C / hr, and the hydrogen generated up to 250°C is measured by gas chromatography. In this way, the amount of released hydrogen is measured using temperature-ramp analysis, and the cumulative value of the amount of hydrogen detected in the temperature range from room temperature to less than 210°C is taken as the amount of diffusible hydrogen. The room temperature may be 0 to 50°C. Here, the hydrogen content is preferably measured after the production of the steel sheet is completed, and more preferably within one week after the production of the steel sheet is completed.
[0038] surface soft layer In a galvanized steel sheet (hereinafter also referred to as base steel sheet) according to one embodiment of the present invention, it is preferable that the base steel sheet has a soft surface layer (located on the base (underlying) of the galvanized steel sheet) on the surface of the base steel sheet. The soft surface layer contributes to suppressing the progression of bending cracks during press forming and vehicle collisions, thereby further improving bending fracture resistance. The soft surface layer means a decarburized layer, and is a surface region having a Vickers hardness of 85% or less of the Vickers hardness of the cross section at 1 / 4 of the sheet thickness. Here, the soft surface layer is formed in a region of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction. The thickness of the soft surface layer is preferably 150 μm or less, more preferably 120 μm or less, and most preferably 100 μm or less. There is no particular lower limit for the thickness of the soft surface layer, but the region where the soft surface layer is formed is preferably 7 μm or more from the surface of the base steel sheet in the sheet thickness direction. Vickers hardness is measured based on JIS Z 2244-1 (2020) at a load of 10 gf.
[0039] Nano-hardness of the soft surface layer When the nano hardness is measured at 300 or more points in a 50 μm × 50 μm area on the sheet surface at 1 / 4 of the sheet thickness depth and 1 / 2 of the sheet thickness depth from the surface of the base steel sheet, the ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at 1 / 4 of the sheet thickness depth of the soft surface layer from the surface of the base steel sheet to the total number of measurements at 1 / 4 of the sheet thickness depth of the soft surface layer is 0.10 or less. In the present invention, in order to obtain excellent bendability during press forming and excellent bending fracture properties during collision, when the nanohardness is measured at 300 or more points in a 50 μm × 50 μm region of the sheet surface at 1 / 4 of the sheet thickness depth of the soft surface layer from the surface of the base steel sheet, the ratio of the number of measurements of nanohardness of 7.0 GPa or more at 1 / 4 of the sheet thickness depth of the soft surface layer from the surface of the base steel sheet is preferably 0.10 or less to the total number of measurements at 1 / 4 of the sheet thickness depth of the soft surface layer. When the ratio of nanohardness of 7.0 GPa or more is 0.10 or less, it means that the ratio of hard structure (martensite, etc.), inclusions, etc. is small, and it is possible to further suppress the generation and connection of voids and crack growth during press forming and collision of hard structure (martensite, etc.), inclusions, etc., and to obtain excellent R / t and SFmax. The ratio of the nano-hardness of the sheet surface at 1 / 4 of the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet to that of 7.0 GPa or more is preferably 0.09 or less, more preferably 0.08 or less, relative to the total number of measurements. The lower limit is not particularly limited, but may be 0.01 or more.
[0040] The standard deviation σ of the nano hardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, and further, the standard deviation σ of the nano hardness of the sheet surface at 1 / 2 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 2.2 GPa or less. In the present invention, in order to obtain excellent bendability during press forming and excellent bending fracture properties during collision, it is preferable that the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, and further, the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 2.2 GPa or less. When the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, and further, the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 2.2 GPa or less, it means that the difference in microscopic hardness is small, and it is possible to further suppress the generation and connection of voids during press forming and collision, and further the growth of cracks, and excellent R / t and SFmax are obtained. A more preferred range of the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the depth in the sheet thickness direction of the soft surface layer from the steel sheet surface is 1.7 GPa or less. The standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the depth in the sheet thickness direction of the soft surface layer from the steel sheet surface is even more preferably 1.6 GPa or less. Although there is no particular lower limit, the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the depth in the sheet thickness direction of the soft surface layer from the steel sheet surface may be 0.1 GPa or more, or may be 0.3 GPa or more. A more preferred range of the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 the depth of the soft surface layer in the sheet thickness direction from the steel sheet surface is 2.1 GPa or less. The standard deviation σ of the nanohardness of the sheet surface at 1 / 2 the depth of the soft surface layer in the sheet thickness direction from the steel sheet surface is even more preferably 2.0 GPa or less. Although there is no particular lower limit, the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 the depth of the soft surface layer in the sheet thickness direction from the steel sheet surface may be 0.1 GPa or more, or may be 0.3 GPa or more.
[0041] Here, the nano-hardness of the plate surface at the 1 / 4 and 1 / 2 positions in the plate thickness direction depth is a hardness measured by the following method. First, the plating layer is peeled off. Then, mechanical polishing is performed from the surface of the steel sheet (base steel sheet) to a position 1 / 4 of the thickness of the soft surface layer - 5 μm, buffing is performed with diamond and alumina from the surface of the base steel sheet to a position 1 / 4 of the thickness of the soft surface layer, and colloidal silica polishing is performed. Using a Hysitron tribo-950, the nano hardness is measured with a Berkovich-shaped diamond indenter under the following conditions: load: 500 μN, measurement area: 50 μm x 50 μm, and impact spacing: 2 μm. In addition, the surface soft layer is mechanically polished up to 1 / 2 the depth in the plate thickness direction, buffed with diamond and alumina, and then polished with colloidal silica.Then, using a Hysitron tribo-950, the nano hardness is measured with a Berkovich-shaped diamond indenter under the following conditions: load: 500μN, measurement area: 50μm×50μm, and impact spacing: 2μm.
[0042] Metal plating layer (first plating layer) Furthermore, the galvanized steel sheet according to one embodiment of the present invention preferably has a metal plating layer (first plating layer, pre-plating layer) (note that the metal plating layer (first plating layer) excludes the galvanized layer of a hot-dip galvanized layer and an alloyed hot-dip galvanized layer) on one or both surfaces of the steel sheet (base steel sheet). The metal plating layer is preferably a metal electroplated layer, and the following description will be given taking a metal electroplated layer as an example. By forming a metal electroplating layer on the surface of the steel sheet, the outermost metal electroplating layer contributes to suppressing the occurrence of bending cracks during press forming and vehicle collisions, thereby further improving bending fracture resistance. In the present invention, the thickness of the soft layer can be increased and the axial collapse characteristics can be made very excellent by setting the dew point to above -20°C. In this regard, in the present invention, by having a metal plating layer, even if the soft layer thickness is small at a dew point of -20°C or less, the axial collapse characteristics can be obtained that are equivalent to those in the case of a thick soft layer.
[0043] Metal species of the metal electroplating layer include Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Pt The metal may be any of Au, Hg, Ti, Pb, and Bi, but Fe is more preferable. In the following, an Fe-based electroplating layer will be described as an example, but the following conditions for Fe can be similarly adopted for other metals.
[0044] The adhesion weight of the Fe-based electroplating layer is 0g / m 2 More than 2.0 g / m 2 The upper limit of the coating weight of the Fe-based electroplating layer per side is not particularly limited, but from the viewpoint of cost, the coating weight of the Fe-based electroplating layer per side is set to 60 g / m or more. 2 The coating weight of the Fe-based electroplating layer is preferably 50 g / m 2 More preferably, it is 40 g / m or less. 2 More preferably, it is 30 g / m or less. 2 The following applies.
[0045] The adhesion weight of the Fe-based electroplating layer is measured as follows. A sample of 10 x 15 mm size is taken from the Fe-based electroplated steel sheet and embedded in resin to create a cross-section embedded sample. Three random locations on the cross-section are observed using a scanning electron microscope (SEM) at an accelerating voltage of 15 kV and a magnification of 2000 to 10000 times depending on the thickness of the Fe-based plating layer, and the average thickness of the three fields of view is multiplied by the specific gravity of iron to convert it into the adhesion weight of the Fe-based plating layer per side.
[0046] As the Fe-based electroplating layer, in addition to pure Fe, alloy plating layers such as Fe-B alloy, Fe-C alloy, Fe-P alloy, Fe-N alloy, Fe-O alloy, Fe-Ni alloy, Fe-Mn alloy, Fe-Mo alloy, Fe-W alloy, etc. can be used. The composition of the Fe-based electroplating layer is not particularly limited, but it is preferable that the composition contains one or more elements selected from the group consisting of B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V and Co in a total of 10 mass% or less, with the balance being Fe and unavoidable impurities. By making the amount of elements other than Fe 10 mass% or less in total, it is possible to prevent a decrease in electrolysis efficiency and form the Fe-based electroplating layer at low cost. In the case of an Fe-C alloy, the content of C is preferably 0.08 mass% or less.
[0047] Zinc plating layer (second plating layer) Plating weight per side is 20~120g / m 2 The zinc plating layer has a plating weight of 20g / m2 on each side. 2 The coating weight of the zinc-plated layer on one side is preferably 120 g / m or more. 2 The coating weight is preferably 20 g / m or less. 2 If the thickness is less than 20g / m, it may be difficult to ensure corrosion resistance. Therefore, the coating weight of the zinc coating layer on one side should be 20g / m 2 It is preferable that the amount is equal to or more than that. On the other hand, 120g / m 2 If the coating weight exceeds 120g / m2, the resistance to peeling of the coating may deteriorate. 2 It is preferable that:
[0048] The Fe content of the zinc plating layer (second plating layer) is 8 to 15% by mass. Moreover, the zinc plating layer preferably contains Fe in a mass% of 8% or more. Moreover, the zinc plating layer preferably contains Fe in a mass% of 15% or less. When the Fe content in the zinc plating layer is 8% or more by mass, it can be said that an Fe-Zn alloy layer is sufficiently obtained. It is preferably 9% or more, more preferably 10% or more. On the other hand, when the Fe content exceeds 15%, the plating adhesion is deteriorated, and a defect called powdering may occur during pressing. Therefore, the Fe content is preferably 15% or less. It is more preferably 14% or less, and further preferably 13% or less.
[0049] The thickness of the galvanized steel sheet of the present invention is not particularly limited, but is preferably 0.8 mm or more, more preferably 1.0 mm or more, and is preferably 3.2 mm or less, more preferably 2.6 mm or less.
[0050] [Manufacturing method of zinc-plated steel sheets] Next, a method for producing a zinc-plated steel sheet according to the present invention will be described. Steel adjusted to the above chemical composition is melted in a converter or the like, and made into a slab by continuous casting, etc. This slab is hot-rolled to form a hot-rolled steel sheet, which is then pickled and cold-rolled to produce a cold-rolled steel sheet, which is then annealed and plated in a continuous hot-dip galvanizing line (CGL). Specifically, the method for producing a galvanized steel sheet of the present invention includes a hot rolling step of hot rolling a steel slab having the above-mentioned composition to obtain a hot rolled steel sheet having a structure in which the total area ratio of bainite and martensite is 80% or more, a pickling step of pickling the obtained hot rolled steel sheet, a cold rolling step of cold rolling at a cold reduction of 30% or more and 80% or less after the pickling step to obtain a cold rolled steel sheet, a continuous annealing step of continuous annealing the cold rolled steel sheet, and a continuous annealing step of cooling the obtained cold rolled annealed steel sheet at an average cooling rate of 3°C in a temperature range of 750 to 550°C after the continuous annealing step. the first cooling step of cooling the plated steel sheet after the first cooling step at a rate of 3°C / s or more and 50°C / s or less to 550°C or less, a galvanizing step of performing a galvanizing treatment after the first cooling step, a second cooling step of cooling the plated steel sheet after the galvanizing step to 100°C or less, and a reheating step of holding the plated steel sheet after the second cooling step in a temperature range of 150°C or more and 450°C or less for 10 seconds to 72 hours or less, wherein the continuous annealing step has an average heating rate of 3°C / s or more at 500 to 700°C, and has a temperature range of 780°C or more and less than 940°C, and has a D in the following formula (1) of 1.0×10 -6 Above 8.0×10 -6 The following conditions are met, and the temperature is heated to a maximum temperature of 780°C or higher and (Ac3 point -20°C) or lower, and the hydrogen concentration in the annealing furnace in the temperature range of 780°C or higher is 1 vol% or higher and 20 vol% or lower.
number
[0051] Each condition will be explained below. In the following explanation, the temperature is the steel sheet surface temperature unless otherwise specified. The steel sheet surface temperature can be measured using a radiation thermometer or the like. The average cooling rate is defined as (surface temperature before cooling - surface temperature after cooling) / cooling time. The average heating rate is defined as (surface temperature after heating - surface temperature before heating) / heating time.
[0052] Steel slab manufacturing The smelting method for producing the steel slab is not particularly limited, and known smelting methods such as converters and electric furnaces can be used. Secondary refining may also be performed in a vacuum degassing furnace. After that, it is preferable to make a slab (steel material) by a continuous casting method from the viewpoints of productivity and quality. Also, a slab may be made by known casting methods such as an ingot casting-blooming rolling method and a thin slab continuous casting method.
[0053] Hot rolling Hot-rolled steel sheet structure: The total area ratio of bainite and martensite is 80% or more In the present invention, hot rolling is performed so that the total area ratio of bainite and martensite in the structure of the obtained hot-rolled steel sheet is 80% or more. In the hot-rolled structure, if ferrite, pearlite, etc. are present as phases other than bainite and martensite, the distribution of Mn concentration at the hot-rolling stage is likely to be non-uniform. If such a hot-rolled steel sheet is used, austenitization occurs preferentially from the areas with high Mn concentration in the final annealing process, the grain size of martensite becomes coarse, and the desired amount of high-Mn ferrite cannot be obtained due to excessive distribution of Mn during annealing. Therefore, the total area ratio of bainite and martensite in the structure of the hot-rolled steel sheet is set to 80% or more.
[0054] The hot rolling conditions are not particularly limited as long as the structure of the hot-rolled steel sheet has a total area ratio of bainite and martensite of 80% or more. For example, the following conditions can be applied as the slab heating temperature, finish rolling temperature, average cooling rate in the temperature range of 800 to 600°C, and coiling temperature.
[0055] Slab heating To hot roll a steel slab, a method of rolling the slab after heating, a method of directly rolling the slab after continuous casting without heating, a method of rolling the slab after continuous casting after subjecting it to a short-term heat treatment, etc. may be applied. The slab heating temperature may be 1100°C or higher. Also, the slab heating temperature may be 1320°C or lower.
[0056] Finish rolling temperature: 800℃ or higher Average cooling rate in the temperature range of 800 to 600°C: 30°C / s or more If the finish rolling end temperature is less than 800°C or the average cooling rate in the temperature range of 800 to 600°C is less than 30°C / s, excessive ferrite is generated during rolling or cooling, making it difficult to achieve a total area ratio of bainite and martensite of 80% or more in the hot-rolled sheet structure. Therefore, it is preferable to set the finish rolling temperature to 800°C or more and the average cooling rate in the temperature range of 800 to 600°C to 30°C / s or more. From the viewpoint of equipment costs, the upper limit is preferably 200°C / s or less.
[0057] Winding temperature: 300℃ to 550℃ If the coiling temperature is less than 300°C, the shape of the hot-rolled steel sheet will deteriorate, affecting the sheet passing properties during the subsequent rolling and annealing. Therefore, the coiling temperature is preferably 300°C or higher. On the other hand, if the coiling temperature exceeds 550°C, ferrite and pearlite are generated after coiling, making it difficult to achieve a hot-rolled sheet structure with a total area ratio of bainite and martensite of 80% or more. Therefore, the coiling temperature is preferably 550°C or less.
[0058] Pickling The hot-rolled steel sheet thus obtained is subjected to pickling. The pickling conditions are not particularly limited.
[0059] Cold rolling Cold rolling reduction: 30% to 80% The cold rolling conditions require a cold reduction (cumulative reduction) of 30% or more in order to generate recrystallized ferrite during annealing and ensure workability. On the other hand, if the cold reduction exceeds 80%, the rolling load increases excessively, hindering productivity. Therefore, the cold reduction is set to 30% or more and 80% or less. The cold reduction is preferably 40% or more. Also, the cold reduction is preferably 70% or less.
[0060] (Metal plating (metal electroplating, first plating) process) In one embodiment of the present invention, a first plating step may be included in which metal plating is applied to one or both sides of the steel sheet after the cold rolling step and before the continuous annealing step to form a metal plating layer (first plating layer). For example, the surface of the cold-rolled steel sheet obtained as described above may be subjected to a metal electroplating treatment to obtain a pre-annealed metal electroplated steel sheet having a pre-annealed metal electroplating layer formed on at least one surface thereof. Note that the metal plating referred to here does not include zinc plating (second plating). The metal electroplating method is not particularly limited, but as described above, it is preferable to form a metal electroplating layer on the steel sheet (base steel sheet), and therefore it is preferable to carry out a metal electroplating process. For example, in the case of an Fe-based electroplating bath, a sulfuric acid bath, a hydrochloric acid bath, or a mixture of both can be used. The coating weight of the metal electroplating layer before annealing can be adjusted by the current application time, etc. Note that the metal electroplated steel sheet before annealing means that the metal electroplating layer has not been subjected to a continuous annealing process, and does not exclude forms in which a hot-rolled steel sheet before metal electroplating, a pickled sheet after hot rolling, or a cold-rolled steel sheet has been annealed in advance.
[0061] Here, the metal species of the electroplating layer are Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Pt Any of Au, Hg, Ti, Pb, and Bi can be used, but Fe is more preferable, so a method for producing Fe-based electroplating is described below.
[0062] The Fe ion content in the Fe-based electroplating bath before the start of current application is 2+ The content of Fe ions in the Fe-based electroplating bath is preferably 0.5 mol / L or more. 2+ A sufficient amount of Fe can be obtained if the Fe ion content in the Fe-based electroplating bath before the start of current application is 0.5 mol / L or more. In order to obtain a sufficient amount of Fe, the Fe ion content in the Fe-based electroplating bath before the start of current application is preferably 2.0 mol / L or less.
[0063] The Fe-based electroplating bath may contain Fe ions and at least one element selected from the group consisting of B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V, and Co. The total content of these elements in the Fe-based electroplating bath is preferably such that the total content of these elements in the Fe-based electroplating layer before annealing is 10 mass% or less. The metal elements may be contained as metal ions, and the nonmetal elements may be contained as part of boric acid, phosphoric acid, nitric acid, organic acid, etc. The iron sulfate plating solution may also contain a conductivity aid such as sodium sulfate or potassium sulfate, a chelating agent, or a pH buffer.
[0064] Other conditions for the Fe-based electroplating bath are not particularly limited. The temperature of the Fe-based electroplating solution is preferably 30°C or higher, and preferably 85°C or lower, in consideration of the ability to maintain a constant temperature. The pH of the Fe-based electroplating bath is not particularly specified, but is preferably 1.0 or higher in order to prevent a decrease in current efficiency due to hydrogen generation, and is preferably 3.0 or lower in consideration of the electrical conductivity of the Fe-based electroplating bath. The current density is 10 A / dm from the viewpoint of productivity. 2 From the viewpoint of easily controlling the deposition weight of the Fe-based electroplating layer, it is preferable to set the current to 150 A / dm or more. 2 The sheet threading speed is preferably 5 mpm or more from the viewpoint of productivity, and is preferably 150 mpm or less from the viewpoint of stable control of the adhesion amount.
[0065] As a treatment before the Fe-based electroplating treatment, a degreasing treatment and water washing for cleaning the steel sheet surface, and further, a pickling treatment and water washing for activating the steel sheet surface can be performed. Following these pretreatments, the Fe-based electroplating treatment is performed. The method of the degreasing treatment and water washing is not particularly limited, and a normal method can be used. In the pickling treatment, various acids such as sulfuric acid, hydrochloric acid, nitric acid, and mixtures thereof can be used. Among them, sulfuric acid, hydrochloric acid, or mixtures thereof are preferable. The concentration of the acid is not particularly specified, but considering the ability to remove the oxide film and the prevention of roughness (surface defects) due to excessive pickling, it is preferable to be about 1 to 20 mass%. In addition, the pickling treatment solution may contain an antifoaming agent, a pickling promoter, a pickling inhibitor, etc.
[0066] Continuous Annealing Average heating rate at 500-700℃: 3℃ / s or more After the above cold rolling, the obtained cold rolled steel sheet is subjected to continuous annealing. In continuous annealing, if the average heating rate at 500 to 700°C is less than 3°C / s, excessive recrystallization and grain growth of ferrite occurs, resulting in coarsening of the structure, making it impossible to reduce the average crystal grain size of martensite to 10 µm or less. Therefore, the average heating rate at 500 to 700° C. is set to 3° C. / s or more. The average heating rate is preferably 5° C. / s or more. There is no particular upper limit, but the average heating rate is preferably 100° C. / s or less, and more preferably 50° C. / s or less.
[0067] Maximum temperature reached: 780℃ or higher, (Ac3 point -20℃) or lower If the maximum temperature in continuous annealing is less than 780°C, the generation of austenite will be insufficient and the desired amount of martensite will not be obtained after annealing, whereas if the temperature exceeds (Ac3 point - 20°C), excessive austenite will be generated and the desired amount of ferrite will not be obtained. Therefore, the maximum temperature is set to 780°C or more and (Ac3 point - 20°C) or less. Here, the Ac3 point is determined by the following formula (3). Ac3(℃)=910-203×[%C] 1 / 2-15.2×[%Ni]+44.7×[%Si]+104×[%V]+31.5×[%Mo]...Equation (3) In formula (3), [%C], [%Ni], [%Si], [%V], and [%Mo] respectively refer to the C content, Ni content, Si content, V content, and Mo content (mass%) of the steel sheet, and elements that are not contained are set to zero (0 mass%).
[0068] D: 1.0×10 -6 Above 8.0×10 -6 below
number
[0069] Hydrogen concentration in the annealing furnace at temperatures above 780°C: 1 vol% to 20 vol% If the hydrogen concentration in the annealing furnace in the temperature range of 780°C or higher is less than 1 vol%, the plating property is deteriorated and non-plating occurs. On the other hand, if this hydrogen concentration exceeds 20 vol%, the diffusible hydrogen concentration in the steel increases, causing deterioration of hydrogen embrittlement resistance and deterioration of ductility of the steel. Therefore, the hydrogen concentration in the annealing furnace in the temperature range of 780°C or higher is set to 1 vol% or more and 20 vol% or less. This hydrogen concentration is preferably 3 vol% or more. Also, this hydrogen concentration is preferably 15 vol% or less.
[0070] Dew point of the atmosphere during the continuous annealing process (annealing atmosphere): -30°C or higher In one embodiment of the present invention, the dew point of the atmosphere (annealing atmosphere) in the continuous annealing step is preferably -30°C or higher. By performing annealing with the dew point of the annealing atmosphere in the continuous annealing step being -30°C or higher, the decarburization reaction is promoted and the surface soft layer can be formed deeper. The dew point of the annealing atmosphere in the continuous annealing step is more preferably -25°C or higher, even more preferably higher than -20°C, even more preferably -15°C or higher, and even more preferably -5°C or higher. Although there is no particular upper limit for the dew point of the annealing atmosphere in the continuous annealing step, in order to suitably prevent oxidation of the surface of the Fe-based electroplating layer and to improve the plating adhesion when a zinc plating layer is provided, the dew point of the annealing atmosphere in the continuous annealing step is preferably 30°C or lower.
[0071] 1st cooling Average cooling rate after continuous annealing: 3℃ / s to 50℃ / s in the temperature range of 750 to 550℃ The cold-rolled annealed steel sheet obtained after the continuous annealing is subjected to a cooling treatment. Here, high Mn ferrite is generated by transformation from austenite in which Mn is concentrated during two-phase annealing. If the average cooling rate in the temperature range of 750 to 550 ° C. where ferrite is generated during cooling exceeds 50 ° C. / s, ferrite transformation is suppressed and high Mn ferrite is not obtained. On the other hand, if the cooling rate is less than 3 ° C. / s, pearlite is generated during cooling and a desired amount of martensite is not obtained. Therefore, the average cooling rate in the temperature range of 750 to 550 ° C. after annealing is set to 3 ° C. / s or more and 50 ° C. / s or less. The average cooling rate in the temperature range of 750 to 550 ° C. after annealing is preferably 5 ° C. / s or more. In addition, the average cooling rate in the temperature range of 750 to 550 ° C. after annealing is preferably 30 ° C. / s or less.
[0072] Moreover, the cooling stop temperature in the cooling (first cooling) after this annealing is set to 550°C or lower, because if it exceeds 550°C, excessive pearlite will be generated and the desired structure will not be obtained.
[0073] Zinc plating treatment In the present invention, after the first cooling step, a galvanizing treatment is performed. As the galvanizing treatment, a hot-dip galvanizing treatment can be adopted. The conditions of the hot-dip galvanizing treatment are not particularly limited.
[0074] Alloying treatment after zinc plating Temperature range: 480-560℃, treatment time: 5-60s After the zinc plating treatment, an alloying treatment may be carried out. When alloying is performed after zinc plating, if the alloying temperature is less than 480°C or the time is less than 5s, the alloying of the plating does not proceed sufficiently. On the other hand, if the alloying temperature is more than 560°C or the time is more than 60s, the alloying proceeds excessively and the powdering property of the plating decreases. Therefore, when alloying is performed, the alloying conditions are 480-560°C and 5-60s. The temperature range in which the alloying treatment is carried out is preferably 500° C. or higher. The temperature range in which the alloying treatment is carried out is preferably 540° C. or lower. The time period in which the alloying treatment is carried out is preferably 10 s or longer. The time period in which the alloying treatment is carried out is preferably 40 s or shorter.
[0075] In the galvanized steel sheet obtained by the above-mentioned zinc plating and alloying treatment, the coating weight of the coating and the Fe content in the coating layer are not particularly limited. For example, the coating weight of the coating is 20 g / m per side. 2 The plating weight can be 120g / m2 or more per side. 2 The Fe content may be 8% or more by mass. The Fe content may be 15% or less by mass.
[0076] 2nd cooling Cool to below 100℃ After the above plating or alloying treatment is carried out (after the zinc plating step or after the alloying treatment step), the plated steel sheet is cooled to a cooling stop temperature of 100° C. or lower. If the cooling stop temperature exceeds 100°C, a sufficient amount of martensite is not generated when cooling is stopped, and a large amount of austenite remains, so that the effect of subsequent reheating cannot be obtained sufficiently. Therefore, the cooling stop temperature in the cooling after the alloying treatment is set to 100°C or less. This cooling stop temperature is preferably 50°C or less.
[0077] Reheating Hold for 10 seconds to 72 hours in the temperature range of 150℃ to 450℃ After the plated steel sheet that has been subjected to the above plating or alloying treatment is cooled to 100°C or less (after the second cooling step), it is reheated and held at a temperature range of 150°C to 450°C for 10 seconds to 72 hours. This tempers the martensite and softens it, reducing the hardness difference between ferrite and martensite and improving local deformation characteristics. Furthermore, it is also possible to reduce the amount of diffusible hydrogen in the steel. If the reheating temperature (tempering temperature) is less than 150°C or the holding time is less than 10 seconds, the tempering of martensite and the reduction of the amount of diffusible hydrogen in the steel will be insufficient. On the other hand, if the reheating temperature (tempering temperature) is more than 450°C or the holding time is more than 72 hours, the martensite will be excessively tempered and the desired strength will not be obtained. Therefore, in the reheating treatment, the temperature is held in the range of 150°C to 450°C for 10 seconds to 72 hours.
[0078] In this manner, the galvanized steel sheet of the present invention is obtained.
[0079] [Part] Next, the members of the present invention will be described. A member according to an embodiment of the present invention is a member made of the above-mentioned galvanized steel sheet (as a raw material). For example, the raw material galvanized steel sheet is subjected to at least one of forming and joining to form the member. Here, the above-mentioned galvanized steel sheet has excellent uniform deformation characteristics and local deformation characteristics, and has a tensile strength TS of 980 MPa or more. Therefore, the member according to one embodiment of the present invention has excellent uniform deformation characteristics and local deformation characteristics, and has a tensile strength TS of 980 MPa or more. Therefore, the member according to one embodiment of the present invention is particularly suitable as a material for automobile parts.
[0080] [Material manufacturing method] Next, a method for manufacturing a member according to one embodiment of the present invention will be described. A method for producing a component according to one embodiment of the present invention includes a step of subjecting the above-mentioned galvanized steel sheet to at least one of forming and joining to form a component. Here, the molding method is not particularly limited, and for example, a general processing method such as press processing can be used. The joining method is also not particularly limited, and for example, general welding such as spot welding, laser welding, and arc welding, rivet joining, crimp joining, etc. The molding conditions and joining conditions are not particularly limited, and may be in accordance with ordinary methods. EXAMPLES
[0081] (galvanized steel sheet) <Example 1> Steel having the composition shown in Table 1, the balance being Fe and unavoidable impurities, was melted in a converter and made into a steel slab by a continuous casting method. The obtained steel slab was hot-rolled to a thickness of 3.0 mm under the conditions shown in Table 2. Next, the obtained hot-rolled steel sheet was pickled and then cold-rolled to a thickness of 1.4 mm to produce a cold-rolled steel sheet, which was then subjected to annealing. The annealing was performed in a continuous hot-dip galvanizing line (CGL). The sheet passing conditions for the CGL are shown in Table 2. The hot-dip galvanizing treatment conditions were as follows: the steel sheet was immersed in a coating bath at a bath temperature of 475°C, then pulled out, and the coating amount was adjusted in various ways by gas wiping, and then alloying treatment was performed. Note that some steel sheets were made into hot-dip galvanized steel sheets without alloying treatment. The cooling stop temperature in the first cooling step was 500°C.
[0082] [Table 1]
[0083] [Table 2]
[0084] The tensile properties and steel sheet structure of the zinc-coated steel sheets obtained as described above were measured as follows. The tensile properties were measured using JIS No. 5 test pieces (JIS Z2201) taken perpendicular to the rolling direction of the steel sheet at a strain rate of 10 -3 Tensile tests were conducted at 1000 rpm / s to measure the tensile strength (TS), total elongation (T.El), and ultimate deformability. The ultimate deformability εl was calculated by measuring the width W and thickness T of the fracture surface of the tensile test piece after the tensile test, measuring the width W0 and thickness T0 of the tensile test piece before the tensile test, and using the following formula (2). εl=-{ln(W / W0)+ln(T / T0)} ···(2) Here, εl is the ultimate deformability, W is the width (mm) of the fracture surface of the tensile test specimen after the tensile test, W0 is the width (mm) of the tensile test specimen before the tensile test, T is the thickness (mm) of the fracture surface of the tensile test specimen after the tensile test, and T0 is the thickness (mm) of the tensile test specimen before the tensile test.
[0085] The method for measuring the structure (cross-sectional structure of the steel plate) was to first reveal the structure using a 1% by mass nital solution, and then observe the 1 / 4 position of the plate thickness (a position at a depth equivalent to one-quarter of the plate thickness from the surface) at a magnification of 3000x using a scanning electron microscope (SEM). The area ratios of martensite, ferrite, pearlite, and bainite were quantified from the photographed structure. The volume fraction of retained austenite was determined by polishing the steel plate to 1 / 4 of the plate thickness direction and measuring the diffracted X-ray intensity at this 1 / 4 plate thickness surface. CoKα radiation was used as the incident X-ray, and the intensity ratios were calculated for all combinations of the integrated peak intensities of the {111}, {200}, {220}, and {311} planes of the retained austenite phase and the {110}, {200}, and {211} planes of the ferrite phase, and the average of these was taken as the volume fraction (area fraction) (%) of retained austenite. The average grain size of martensite was measured by observing the specimen at a magnification of 3000 times using a SEM and taking a structural photograph. The grain size was determined to be between 5000 and 10000 μm. 2 The area and number of martensite grains in the field of view were determined, and the area per martensite grain was calculated by dividing the area by the number of grains. The martensite grains were approximated as a square, and one side of the square was taken as the average grain size.
[0086] The ratio of the area ratio of low Mn ferrite and high Mn ferrite to the area ratio of the entire ferrite was calculated as follows. First, a sample was taken from the cross section of the steel plate parallel to the rolling direction, and the observation surface was mechanically polished to a mirror finish. After that, FE-EPMA analysis was performed at the 1 / 4 position of the plate thickness to measure 5000 to 10000 μm 2 The distribution of Mn concentration in the field of view was measured at intervals of 0.1 μm. From these, measurement points corresponding to the positions of ferrite were extracted, and further measurement points where the concentration was 0.80 to 0.95 times or 1.05 to 2.5 times the Mn concentration of the steel were extracted. The ratios of the number of measurement points where the Mn concentration was 0.80 to 0.95 times or 1.05 to 2.5 times the Mn concentration of the steel to the number of measurement points of the entire ferrite were calculated as the ratios of the area ratio of low Mn ferrite and high Mn ferrite to the area ratio of the entire ferrite, respectively. The location of ferrite at the points where the Mn FE-EPMA analysis was performed was identified by measuring the C concentration distribution with FE-EPMA.
[0087] The amount of diffusible hydrogen in steel was measured using the following method. First, a 5 x 30 mm test piece was cut out from the plated steel sheet. Next, a router was used to remove the plating from the surface of the test piece and it was placed in a quartz tube. Next, the inside of the quartz tube was purged with Ar, after which the temperature was raised at 200°C / hr and the hydrogen generated up to 250°C was measured by gas chromatography. In this way, the amount of released hydrogen was measured using temperature-programmed analysis, and the cumulative value of the amount of hydrogen detected in the temperature range from room temperature (25°C) to less than 210°C was taken as the amount of diffusible hydrogen. Here, the hydrogen amount was measured after the completion of the production of the steel sheet (after one week).
[0088] The results are shown in Table 3.
[0089] [Table 3]
[0090] All of the examples of the present invention exhibit high strength with a tensile strength of 980 MPa or more, a ductility index TS×T.El of 17,000 MPa·%, and excellent deformation characteristics with an ultimate deformability εl of 0.70 or more.
[0091] <Example 2> Steel having the composition shown in Table 1, the balance being Fe and unavoidable impurities, was melted in a converter and made into a steel slab by a continuous casting method. The obtained steel slab was hot-rolled to a thickness of 3.0 mm under the conditions shown in Table 4. Next, the obtained hot-rolled steel sheet was pickled and then cold-rolled to a thickness of 1.4 mm to produce a cold-rolled steel sheet, which was then subjected to annealing. The annealing was performed in a continuous hot-dip galvanizing line (CGL). The sheet passing conditions for the CGL are shown in Table 4. The hot-dip galvanizing treatment conditions were as follows: the steel sheet was immersed in a coating bath at a bath temperature of 475°C, then pulled out, and the coating amount was adjusted in various ways by gas wiping, and then alloying treatment was performed. Note that some steel sheets were made into hot-dip galvanized steel sheets without alloying treatment. The cooling stop temperature in the first cooling step was 500°C.
[0092] For the zinc-plated steel sheets obtained as described above, the tensile properties (tensile strength (TS), total elongation (T.El), ultimate deformability), steel sheet structure, and amount of diffusible hydrogen in steel were measured in the same manner as in Example 1.
[0093] In addition, a U-bend + close bending test, a V-bend + orthogonal VDA bending test, and an axial crushing test were performed according to the following procedures.Then, the limit spacer thickness (ST) in the U-bend + close bending test, the stroke at maximum load (SFmax) measured in the V-bend + orthogonal VDA bending test, and the presence or absence of fracture (visual cracks) in the axial crushing test were evaluated according to the following criteria.
[0094] ·ST 〇:4.0mm≧ST
[0095] ·SFmax ○: 26.5mm≦SFmax
[0096] - Presence or absence of axial crushing fracture (exterior cracks) ⊚: No external cracks were observed in the sample after the axial crush test. ◯: One or less external cracks were observed on the sample after the axial crush test.
[0097] U-bend + close bend test The U-bend + close bending test was carried out as follows. From the obtained galvanized steel sheet, a 60 mm × 30 mm test piece was taken by shearing and edge grinding. Here, the 60 mm side is parallel to the width (C) direction. The test piece was prepared by U-bending (primary bending) in the width (C) direction with the rolling (L) direction as the axis with a curvature radius / sheet thickness of 4.2. In the U-bending (primary bending), as shown in Figure 1 (a), a punch B1 was pressed into the steel sheet placed on a roll A1 to obtain a test piece T1. Next, as shown in Figure 1 (b), the test piece T1 placed on the lower die A2 was subjected to close bending (secondary bending) in which it was crushed by the upper die B2. In Figure 1 (a), D1 indicates the width (C) direction and D2 indicates the rolling (L) direction. Note that a spacer S, which will be described later, was inserted between the test pieces.
[0098] The U-bending conditions in the U-bending + close bending test are as follows. Test method: Roll support, punch intrusion Punch tip R: 5.0mm Roll and punch clearance: Sheet thickness + 0.1 mm Stroke speed: 10mm / min Bending direction: perpendicular to rolling (C) direction The conditions for the U-bend + close bending test are as follows: Spacer thickness: Varies in 0.5mm increments Test method: Die support, punch push Molding load: 10ton Test speed: 10mm / min Holding time: 5s Bending direction: perpendicular to rolling (C) direction
[0099] The above U-bend + close bending test was performed three times, and the critical spacer thickness (ST) was evaluated when no cracks occurred all three times. In addition, using a Leica stereo microscope, cracks with a length of 200 μm or more at 25x magnification were judged to be cracks. ST is an index for evaluating the fracture resistance properties during a collision (the fracture resistance properties of the vertical wall in an axial crushing test). The results are shown in Table 5.
[0100] V-bend + orthogonal VDA bend test The V-bend + orthogonal VDA bend test is carried out as follows. From the obtained galvanized steel sheet, a 60 mm × 65 mm test piece was taken by shearing and edge grinding. Here, the 60 mm side is parallel to the rolling (L) direction. The test piece was prepared by bending the steel sheet 90° (primary bending) in the rolling (L) direction with the width (C) direction as the axis at a curvature radius / sheet thickness of 4.2. In the 90° bending (primary bending), as shown in Figure 2 (a), a punch B3 was pressed into the steel sheet placed on a die A3 with a V groove to obtain a test piece T1. Next, as shown in Figure 2 (b), a punch B4 was pressed into the test piece T1 placed on a support roll A4 so that the bending direction was perpendicular to the rolling direction, and an orthogonal bending (secondary bending) was performed. In Figures 2 (a) and 2 (b), D1 indicates the width (C) direction, and D2 indicates the rolling (L) direction.
[0101] The V-bending conditions in the V-bending + orthogonal VDA bending test are as follows: Test method: Die support, punch push Molding load: 10ton Test speed: 30mm / min Holding time: 5s Bending direction: Rolling (L) direction
[0102] The VDA bending conditions in the V-bending + orthogonal VDA bending test are as follows: Test method: Roll support, punch intrusion Roll diameter: φ30mm Punch tip R: 0.4 mm Distance between rolls: (sheet thickness x 2) + 0.5 mm Stroke speed: 20mm / min Test piece size: 60mm x 60mm Bending direction: perpendicular to rolling (C) direction
[0103] The stroke at maximum load is determined from the stroke-load curve obtained when the VDA bending is performed. The average stroke at maximum load when the V bending + orthogonal VDA bending test is performed three times is taken as SFmax (mm). SFmax is an index for evaluating fracture resistance during a collision (fracture resistance of the bent ridge in an axial crushing test). The results are shown in Table 5.
[0104] Axial Crush Test From the obtained galvanized steel sheet, 160 mm× 200 mm test pieces were taken by shearing. 160 The side of 80 mm is parallel to the rolling (L) direction. The hat-shaped member 10 shown in Fig. 3(a) and Fig. 3(b) was produced by forming (bending) the hat-shaped member 10 to a depth of 40 mm using a die having a punch shoulder radius of 5.0 mm and a die shoulder radius of 5.0 mm. The steel plate used as the material for the hat-shaped member was cut into 80 mm x 80 mm pieces. 200 The steel plate 20 was then separately cut to a size of 1 mm. The cut-out steel plate 20 and the hat-shaped component 10 were then spot welded to produce a test component 30 as shown in Fig. 3(a) and Fig. 3(b). Fig. 3(a) is a front view of the test component 30 produced by spot welding the hat-shaped component 10 and the steel plate 20. Fig. 3(b) is a perspective view of the test component 30. The position of the spot welds 40 was such that the edge of the steel plate and the weld were 10 mm apart, and the gap between the welds was 10 mm, as shown in Fig. 3(b). 45 The interval between the test members 30 and the base plate 50 was set to 1 mm. Next, as shown in FIG. 3(c), the test member 30 was joined to the base plate 50 by TIG welding to prepare a sample for the axial crush test. Next, the impactor 60 was made to collide with the prepared sample for the axial crush test at a constant velocity of 10 mm / min, and the sample for the axial crush test was crushed by 70 mm. As shown in FIG. 3(c), the crush direction D3 was set to be parallel to the longitudinal direction of the test member 30. The results are shown in Table 5.
[0105] Nano Hardness Measurement In order to obtain excellent bendability during press forming and excellent bending fracture properties during collision, when the nanohardness is measured at 300 or more points in a 50μm×50μm region on the sheet surface at 1 / 4 of the sheet thickness depth from the base steel surface to the soft surface layer, it is more preferable that the ratio of the number of measurements of nanohardness of 7.0GPa or more on the sheet surface at 1 / 4 of the sheet thickness depth from the base steel surface to the soft surface layer is 0.10 or less to the total number of measurements at 1 / 4 of the sheet thickness depth. If the ratio of nanohardness of 7.0GPa or more is 0.10 or less, it means that the ratio of hard structures (martensite, etc.), inclusions, etc. is small, so it is possible to further suppress the generation and connection of voids and the development of cracks in hard structures (martensite, etc.) and inclusions during press forming and collision, and excellent ST and SFmax are obtained.
[0106] After the plating was removed, the steel sheet (base steel sheet) was mechanically polished from the surface to a position 1 / 4 of the way down to the thickness direction of the soft surface layer at -5μm, and then buffed with diamond and alumina from the surface of the base steel sheet to a position 1 / 4 of the way down to the thickness direction of the soft surface layer, followed by colloidal silica polishing. Using a Hysitron tribo-950, a Berkovich-shaped diamond indenter was used. Load: 500μN Measurement area: 50μm x 50μm Dot spacing: 2μm A total of 512 nano-hardness points were measured under the above conditions.
[0107] Next, the surface soft layer was mechanically polished to a position halfway down the thickness direction, buffed with diamond and alumina, and polished with colloidal silica. Load: 500μN Measurement area: 50μm x 50μm Dot spacing: 2μm A total of 512 nano-hardness points were measured under the above conditions.
[0108] [Table 4]
[0109] [Table 5]
[0110] All of the examples of the present invention exhibited high strength with a tensile strength of 980 MPa or more, and excellent deformation characteristics with a ductility index TS×T.El of 17,000 MPa·% or more and an ultimate deformability εl of 0.70 or more.
[0111] Furthermore, as shown in Table 5, in all of the examples of the present invention, the limit spacer thickness (ST) in the U-bend + close contact bending test and the stroke at maximum load (SFmax) measured in the V-bend + orthogonal VDA bending test all passed, and there was no fracture (visual cracking) in the axial crush test. Of Nos. 46, 48, and 52, which had dew points in the range of -30°C to -20°C, No. 46 had a soft layer thickness of 14μm or less, and was judged as "○" for fracture (visual cracks) in the axial crush test. On the other hand, Nos. 48 and 52, which had a soft layer thickness of 14μm or less but had a metal plating layer, were judged as "◎" for fracture (visual cracks) in the axial crush test.
[0112] Furthermore, as shown in Table 5, by performing a metal plating process in the manufacturing conditions and / or setting the dew point in the atmosphere in the continuous annealing process to -5°C or higher, it is possible to obtain a zinc-plated steel sheet in which the ratio of the number of measurements of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness depth of the soft surface layer from the steel sheet surface is 7.0 GPa or more relative to the total number of measurements at 1 / 4 of the sheet thickness depth of the soft surface layer is 0.10 or less, and further, the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness depth of the soft surface layer from the base steel sheet surface is 1.8 GPa or less, and further, the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 of the sheet thickness depth of the soft surface layer from the base steel sheet surface is 2.2 GPa or less, and the fracture (visual crack) in the axial crush test was judged to be "◎", and both the ST and SFmax were excellent.
[0113] (Materials) Using the zinc-plated steel sheet of the present invention, components obtained by forming, components obtained by joining, and components obtained by further forming and joining have been found to have excellent uniform deformation characteristics and localized deformation characteristics and a tensile strength TS of 980 MPa or more, similar to the zinc-plated steel sheet of the present invention, because the zinc-plated steel sheet of the present invention has excellent uniform deformation characteristics and localized deformation characteristics and a tensile strength TS of 980 MPa or more. [Explanation of symbols]
[0114] 10 Hat-shaped member 20. Galvanized steel sheet 30 Test components 40 Spot welds 50 Main plate 60 Impactor A1 Die A2 Support roll A3 Die A4 support roll B1 Punch B2 Punch B3 Punch B4 punch D1 width (C) direction D2 Rolling (L) direction D3 Crushing direction S Spacer T1 test piece
Claims
1. A zinc-plated steel sheet comprising a steel sheet and a zinc-plated layer formed on the steel sheet, The steel plate is In mass percent, C: 0.08% or more and 0.3% or less, Si: 0.5% or more and 3.0% or less, Mn: 2.0% or more and 3.5% or less, P: 0.1% or less, S: 0.01% or less, Al: 0.01% or more and 0.1% or less, N: 0.015% or less; The balance is Fe and unavoidable impurities, The structure at 1 / 4 of the plate thickness from the surface is as follows: The area ratio of ferrite is 20% or more and 70% or less, The area ratio of martensite is 30% or more and 80% or less, The area ratio of the structure other than ferrite and martensite is 10% or less, The ferrite is low-Mn ferrite having a Mn concentration of 0.80 to 0.95 times the Mn content of the steel plate; and high Mn ferrite having a Mn concentration of 1.05 to 2.5 times the Mn content of the steel plate, The ratio of the low Mn ferrite to the entire ferrite is 30% or more and 70% or less in terms of area ratio, and The ratio of the high Mn ferrite to the entire ferrite is 30% or more and 70% or less in terms of area ratio, The average grain size of the martensite is 10 μm or less, A zinc-plated steel sheet having a diffusible hydrogen content of 0.30 mass ppm or less.
2. The galvanized steel sheet according to claim 1, wherein the component composition contains one or more selected from the following (A) to (D): (A) in mass %, Ti: 0.1% or less, Nb: 1 or 2 selected from below 0.1% (B) in mass %, Cr: 0.5% or less, Mo: 0.5% or less, V: 0.5% or less, selected from one or more (C) in mass %, B: 0.005% or less (D) in mass %, Ca: 0.005% or less, Sb: 0.03% or less
3. The galvanized steel sheet according to claim 1, which satisfies one or more of the following (1), (2) and (3): (1) When the steel plate has a surface layer in a region of 200 μm or less from the surface of the steel plate in the plate thickness direction, The surface layer has a surface soft layer having a Vickers hardness of 85% or less of the Vickers hardness at a quarter of the plate thickness position, When the nano hardness was measured at 300 points or more in a 50 μm × 50 μm region of the sheet surface at a 1 / 4 position and a 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the steel sheet, The ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer from the steel sheet surface to the total number of measurements at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer is 0.10 or less, Furthermore, the standard deviation σ of the nanohardness of the sheet surface at a position of 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, Furthermore, the standard deviation σ of the nano-hardness of the sheet surface at a position half the depth in the sheet thickness direction of the soft surface layer from the surface of the steel sheet is 2.2 GPa or less. (2) The zinc-plated steel sheet has a metal plating layer formed between the steel sheet and the zinc plating layer on one or both sides thereof. (3) The zinc plating layer is The Fe content is 8 to 15% by mass, and the plating weight per side is 20 to 120 g / m 2 It is.
4. The galvanized steel sheet according to claim 2, which satisfies one or more of the following (1), (2) and (3): (1) When the steel plate has a surface layer in a region of 200 μm or less from the surface of the steel plate in the plate thickness direction, The surface layer has a surface soft layer having a Vickers hardness of 85% or less of the Vickers hardness at a quarter of the plate thickness position, When the nano hardness was measured at 300 points or more in a 50 μm × 50 μm region of the sheet surface at a 1 / 4 position and a 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the steel sheet, The ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer from the steel sheet surface to the total number of measurements at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer is 0.10 or less, Furthermore, the standard deviation σ of the nanohardness of the sheet surface at a position of 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, Furthermore, the standard deviation σ of the nano-hardness of the sheet surface at a position half the depth in the sheet thickness direction of the soft surface layer from the surface of the steel sheet is 2.2 GPa or less. (2) The zinc-plated steel sheet has a metal plating layer formed between the steel sheet and the zinc plating layer on one or both sides thereof. (3) The zinc plating layer is The Fe content is 8 to 15% by mass, and the plating weight per side is 20 to 120 g / m 2 It is.
5. A member made using the galvanized steel sheet according to any one of claims 1 to 4.
6. A hot rolling process in which a steel slab having the composition according to claim 1 or 2 is hot rolled to obtain a hot rolled steel sheet having a structure in which the total area ratio of bainite and martensite is 80% or more; A pickling process for pickling the obtained hot-rolled steel sheet; A cold rolling process in which cold rolling is performed at a cold rolling reduction rate of 30% or more and 80% or less after the pickling process to obtain a cold-rolled steel sheet; A continuous annealing process for subjecting the cold-rolled steel sheet to continuous annealing; After the continuous annealing step, the obtained cold-rolled annealed steel sheet is cooled to 550 ° C. or less at an average cooling rate of 3 ° C. / s or more and 50 ° C. / s or less in a temperature range of 750 to 550 ° C.; a galvanizing step of performing a galvanizing treatment after the first cooling step; A second cooling step of cooling the plated steel sheet after the zinc plating step to 100° C. or less; a reheating step of holding the plated steel sheet after the second cooling step in a temperature range of 150° C. or more and 450° C. or less for 10 seconds or more and 72 hours or less, In the continuous annealing step, The average heating rate at 500 to 700 ° C. is 3 ° C. / s or more, At 780° C. or higher and lower than 940° C., D in the following formula (1) is 1.0×10 -6 Above 8.0 x 10 -6 Satisfy the following: 780℃ or higher, (Ac 3 Heat to a maximum temperature below -20°C. The hydrogen concentration in the annealing furnace in the temperature range of 780° C. or more is set to 1 vol.% or more and 20 vol.% or less, Alternatively, the following (a) and / or (b) are satisfied: A steel plate and a zinc plating layer formed on the steel plate, The steel plate has a structure at a 1 / 4 position of the plate thickness from the surface of the steel plate, The area ratio of ferrite is 20% or more and 70% or less, The area ratio of martensite is 30% or more and 80% or less, The area ratio of the structure other than ferrite and martensite is 10% or less, The ferrite is low-Mn ferrite having a Mn concentration of 0.80 to 0.95 times the Mn content of the steel plate; and high Mn ferrite having a Mn concentration of 1.05 to 2.5 times the Mn content of the steel plate, The ratio of the low Mn ferrite to the entire ferrite is 30% or more and 70% or less in terms of area ratio, and The ratio of the high Mn ferrite to the entire ferrite is 30% or more and 70% or less in terms of area ratio, The average grain size of the martensite is 10 μm or less, A method for producing a galvanized steel sheet, in which the amount of diffusible hydrogen in the steel is 0.30 ppm by mass or less. (a) A metal plating step of forming a metal plating layer by applying metal plating to one or both sides of the cold-rolled steel sheet after the cold rolling step and before the continuous annealing step. (b) An alloying treatment step is included in which the plated steel sheet after the galvanizing step and before the second cooling step is subjected to an alloying treatment in a temperature range of 480 to 560° C. for 5 to 60 s. [0010] Here, in formula (1), t i :T i ℃ or more T i Residence time (s) in the temperature range below +10 ° C. T i (° C.): 780+i×10 (i: an integer from 0 to 15); The residence time t in the temperature range exceeding the maximum temperature i (s) is 0s.
7. The method for producing a galvanized steel sheet according to claim 6, wherein the continuous annealing in the continuous annealing step is performed in an atmosphere with a dew point of −30° C. or higher.
8. A method for manufacturing a component, comprising a step of subjecting the galvanized steel sheet according to any one of claims 1 to 4 to at least one of forming and joining to form a component.
Citation Information
Patent Citations
High strength hot dip galvannealed steel sheet good in workability and its production
JP1999279691A
High-strength steel sheet having excellent rigidity and workability, and its production method
JP2007092132A
High yield ratio and high-strength hot-dip galvanized steel sheet having excellent workability and method of producing the same
JP2010106323A
High strength cold-rolled thin steel sheet and its production method
JP2020111770A
High strength cold rolled steel sheet and high strength galvanized steel sheet having excellent ductility and bendability, and methods for producing same
WO2015141097A1